2012
DOI: 10.1590/s1413-35552012005000028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manual chest compression and descompression maneuver on lung volumes, capnography and pulse oximetry in patients receiving mechanical ventilation

Abstract: Effects of manual chest compression and descompression maneuver on lung volumes, capnography and pulse oximetry in patients receiving mechanical ventilation Efeitos da manobra de compressão e descompressão torácica nos volumes pulmonares, capnografia e oximetria de pulso em pacientes submetidos à ventilação mecânica AbstractObjectives: The aims of this study were to evaluate whether there are changes in lung volumes, capnography, pulse oximetry and hemodynamic parameters associated with manual chest compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 22 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…The lung re-expansion is able to prevent or reverse ventilatory inequality situations, through the variation of intrathoracic pressures or by proper positioning, assisting in the optimization of pulmonary perfusion. The maneuver of thoracic blockade or MCC is indicated in patients that are less cooperative [7]- [9], but its effects are questionable and poorly studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lung re-expansion is able to prevent or reverse ventilatory inequality situations, through the variation of intrathoracic pressures or by proper positioning, assisting in the optimization of pulmonary perfusion. The maneuver of thoracic blockade or MCC is indicated in patients that are less cooperative [7]- [9], but its effects are questionable and poorly studied.…”
Section: Discussionmentioning
confidence: 99%
“…Della Via et al [9] applied the MCC associated with decompression in adults under MV and observed positive effects in the minute volume, tidal volume and oxygenation proving that the improvement attributed to the technique occurs in patients with positive pressure on airways.…”
Section: Discussionmentioning
confidence: 99%
“…The positive response of obese patients to CCDM use in the postoperative period (six hours after surgery) likely derived from hypoventilation correction. According to Via et al [7], CCDM reduced the incidence of pulmonary complications such as hypoventilation and atelectasis, as well as the development of acute hypoxemia after surgery due to pulmonary ventilation restoration, which improved oxygenation and decreased CO2 levels. Unoki et al [23] applied CCDM to 31 mechanically ventilated patients and found Fisioterapia Brasil 2021;22(1):37-48 that this maneuver enabled bronchial hygiene by increasing expiratory time and peak expiratory flow.…”
Section: Systemic Carbon Dioxide Resorption During Videolaparoscopy Smentioning
confidence: 99%
“…Patients assessed in the current study did not present changes in bronchial hygiene needs. Via et al [7] performed bronchial hygiene before CCDM application in all patients; however, Unoki et al [23] performed CCDM without previous bronchial hygiene, which may have reinforced its effects on bronchial hygiene, but not on pulmonary expansion.…”
Section: Lack Of Pulmonary Expansion After Ccdm Application In the Stmentioning
confidence: 99%
See 1 more Smart Citation